Sosialisasi Anti Narkoba Sebagai Bentuk Pencegahan Penyalahgunaan Dikalangan Remaja Smp Negeri 1 Kampa Desa Sawah Baru - Mhd Andry Kurniawan; Robby Ilham Alfayet; Samuel Kristian Julianto; Rizmadan Syah; M. Thoriq Athoilllah; Rizka Nur Fadilah Pulungan; Irma Suryani; Nabila Muthia Indayana; Afra Alifarani; Qayyumidina Silindrika; Annisa Dwita Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Real work lecture (KUKERTA) is a form of community service carried out by students in overcoming village problems that are still unresolved. This service is in the form of socialization to provide information about the dangers of drugs. The rise of drug abuse among teenagers is our main reason for socializing in one of the educational institutions in Sawah Baru Village, namely SMP Negeri 1 Kampa. Teenagers who are still unstable in making decisions are the right targets to become drug users. High curiosity is also one of the factors that teenagers fall into this crime. So that anti-drug socialization must always be promoted to the community, especially teenagers as the next generation of the nation. The purpose of this anti-drug socialization is to provide understanding, direction, and warnings related to drugs that can threaten the lives of both individuals and social.